2007
DOI: 10.1103/physrevb.75.085428
|View full text |Cite
|
Sign up to set email alerts
|

Atomic configurations of Pd atoms in PdAu(111) bimetallic surfaces investigated using the first-principles pseudopotential plane wave approach

Abstract: Atomic configurations of two or three Pd substituents on the Au͑111͒ surface are investigated using the first-principles pseudopotential plane wave approach. Pd atoms are found to form second neighborhoods on PdAu͑111͒. The Pd-d band becomes narrow and well below the Fermi level, very different from those in a Pd film or bulk Pd. Yet the surface Pd atoms are still active and serve as independent attractive centers towards adsorbates. The special ensembles are important for catalysis applications because of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 28 publications
7
51
0
Order By: Relevance
“…1 are presented in Table I. 26 So, in our calculations, PW91 functional is only chosen to reveal the "ensemble effect" for the CO oxidation on Pd ensembles over Au(111) surface. 44 The revised Perdew-Burke-Ernzerhof (RPBE) functional, extrapolation method, and GGA + U type functional offer some improvement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 are presented in Table I. 26 So, in our calculations, PW91 functional is only chosen to reveal the "ensemble effect" for the CO oxidation on Pd ensembles over Au(111) surface. 44 The revised Perdew-Burke-Ernzerhof (RPBE) functional, extrapolation method, and GGA + U type functional offer some improvement.…”
Section: Resultsmentioning
confidence: 99%
“…At low CO pressures and temperature, the isolated Pd monomer is the most stable atomic ensemble on Aubased catalysts with low Pd coverage. 26 Density functional theory (DFT) calculations indicated that the dissociative energy barrier of O 2 strongly depends on the size of contiguous Pd ensembles, and the molecular adsorption state is energetically favorable on the small Pd aggregates (e.g., dimer and trimer). 12,[23][24][25] The experimental investigations suggested a superior reactivity of CO oxidation which is attributed to the role of contiguous Pd atoms on Pd-Au alloy catalyst, and the contiguous Pd sites are crucial to dissociate the O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with the negative formation energy of the alloy in the bulk, 44 with experimental observations, 27 and with recent theoretical results. 45 For the layer-by-layer surfaces, PdAu ͑A͒ and ͑B͒, the formation of aggregates is more energy demanding for the alloys with ͑A͒ configuration than for those with ͑B͒ configuration, up to 0.41 eV. This effect can be explained by the fact that the number of heterometallic ͑Au-Pd͒ contacts in the segregated structures of ͑B͒ composition is larger than that of ͑A͒.…”
Section: A Stability Of the Bimetallic Systemsmentioning
confidence: 92%
“…37 In addition, the mechanisms for preferential nucleation and the role of embedded Pd atoms in Au surface layer have been addressed theoretically by several authors. 25,[38][39][40] The reasons for such contrast differences between Pd and Au atoms were not completely explained. The interpretation of dark regions as Pd species embedded in the Au surface is further supported by an analysis of the electronic contrast by differential conductivity (dI/dV) maps as discussed in Sec.…”
Section: B Cluster Deposition At Different Energy Regimesmentioning
confidence: 99%